Predicting In-hospital Mortality Using D-Dimer in COVID-19 Patients With Acute Ischemic Stroke - Kim, Youngran; Khose, Swapnil; Abdelkhaleq, Rania; Salazar-Marioni, Sergio; Zhang, Guo-Qiang; Sheth, Sunil A. (Frontiers in Neurology, 2021)
Background: Coronavirus disease 2019 (COVID-19) has been associated with coagulopathy, and D-dimer levels have been used to predict disease severity. However, the role of D-dimer in predicting mortality in COVID-19 patients with acute ischemic stroke (AIS) remains incompletely characterized. Methods: We conducted a retrospective cohort study using the Optum® de-identified COVID-19 Electronic Health Record dataset. Patients were included if they were 18 or older, had been hospitalized within 7 days of confirmed COVID-19 positivity from March 1, 2020 - November 30, 2020. We determined the optimal threshold of D-dimer to predict in-hospital mortality and compared risks of in-hospital mortality between patients with D-dimer levels below and above the cutoff. Risk ratios (RRs) were estimated adjusting for baseline characteristics and clinical variables. Results: Among 15,250 patients hospitalized with COVID-19 positivity, 285 presented with AIS at admission (2%). Patients with AIS were older (70 [60-79] vs 64 [52-75], p<0.001) and had greater D-dimer levels at admission (1.42 [0.76-3.96] vs. 0.94 [0.55-1.81] µg/ml FEU, p <0.001). Peak D-dimer level was a good predictor of in-hospital mortality among all patients (c-statistic 0.774 [95% CI 0.764-0.784]) and among patients with AIS (c-statistic 0.751 [95% CI 0.691-0.810]). Among AIS patients, the optimum cutoff was identified at 5.15 µg/ml FEU with 73% sensitivity and 69% specificity. Elevated peak D-dimer level above this cut-off was associated with almost 3 times increased mortality (adjusted RR 2.89 [95% CI 1.87-4.47]). Conclusions: COVID-19 patients with AIS present with greater D-dimer levels. Thresholds for outcomes prognostication should be higher in this population.